Isothermal crystallization kinetics, morphology, and crystalline structure of polypropylene/poly(4‐methyl‐1‐pentene) blends. Issue 1 (23rd January 2020) - Furushima, Yoshitomo; Nakada, Masaru; Masuda, Akihiro; Okada, Kazuma; Iwata, Naoko; Ohkura, Masatoshi
Abstract: The isothermal crystallization kinetics of polypropylene (PP) in poly(4‐methyl‐1‐pentene) blends were investigated by comparing the blend results with those of the PP homopolymer. Fast scanning calorimetry‐optical microscope studies were carried out to determine the crystallization rate and microscale morphology during crystallization from the highly supercooled liquid. The crystallization rate of the blend system was faster than that of the PP homopolymer at temperatures between 50°C and 90°C. Synchrotron small angle X‐ray scattering and transmission electron microscopy results showed that there were no differences in the thickness of lamellar PP or nanoscale PP morphology between the homopolymer and polymer blends. Wide angle X‐ray scattering data revealed that the content ratio of the PP α form and the conformational disordered PP phase did not change between both samples. However, the crystalline lattice size of PP decreased in the blend systems. The increment of crystallization kinetics of the blend system is explained by a Gibbs free energy diagram. Abstract : Fast scanning calorimetry‐optical microscope was used to determine the crystallization rate and microscale morphological change during crystallization from the highly supercooled liquid state. The crystallization rate of the blend system becomes faster than the polypropylene homopolymer at a temperature range from 50°C to 90°C. In addition, the analysis of synchrotron small and wide‐angle X‐ray scattering and transmission electron microscope shows the nanoscale structure and morphology of blends, comparing with that of homopolymer. These behaviors are explained using the Gibbs free energy diagram.